Reframing The SIOP Model To Boost Teachers' Self Efficacy In Bilingual-Like Program: A Practical Concept Of An Alternative Model - Rozanah Katrina Herda; Angga Damayanto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
The need to communicate through English and the desire to practice English in the teaching process has turned a public junior high school in Wonosobo, Indonesia, into one of the schools that hold an